Process automation using machine learning (Data Science Salon, 2020)
"Presented by Raktim Saha - Director, Digital Insights, CGI. The focus of this talk is to showcase how Machine learning and AI is leveraged to radically outperform traditional loan-underwriting acceptance process for one of the largest lenders in US by utilizing a broader set of market, demographic, and various events data. Implementing an automated data-driven process in a large Enterprise and especially in a highly regulated industry has its own challenge spanning from data collection to accuracy of insights, and finally streamline the overall process. The speaker will cover the business, data, and technical aspects of this implementation."--Resource description page